Exploring the Formation and the Structure of Synaptobrevin Oligomers in a Model Membrane. - Han, Jing; Pluhackova, Kristyna; Böckmann, Rainer (Biophysical Journal, 2016)
SNARE complexes have been shown to act cooperatively to enable the synaptic vesicle fusion in neuronal transmission at millisecond timescale. It has previously been suggested that the oligomerization of SNARE complexes required for cooperative action in fusion is mediated by interactions between transmembrane domains (TMDs). We study the oligomerization of synaptobrevin TMD using ensembles of molecular dynamics (MD) simulations at coarse-grained resolution for both the wild-type (WT) and selected mutants. Trimerization and tetramerization of the sybII WT and mutants displayed distinct kinetics depending both on the rate of dimerization and the availability of alternative binding interfaces. Interestingly, the tetramerization kinetics and propensity for the sybII W89A-W90A mutant was significantly increased as compared with the WT; the tryptophans in WT sybII impose sterical restraints on oligomer packing, thereby maintaining an appropriate plasticity and accessibility of sybII to the binding of its cognate SNARE partners during membrane fusion. Higher-order oligomeric models (ranging from pentamer to octamer), built by incremental addition of peptides to smaller oligomers, revealed substantial stability and high compactness. These larger sybII oligomers may induce membrane deformation, thereby possibly facilitating fast fusion exocytosis.